The role of material heritage in activating tourism in Algeria - Sonia, Pr. Bentiba; Azzedine, Bouabid (The International tax journal, 2025)
The interest in cultural heritage is one of the policies adopted by countries to preserve their civilizational or historical heritage, serving as an important means of preserving the collective memory of peoples. Cultural heritage plays a crucial role in attracting tourists, as heritage tourism has experienced significant growth worldwide. As a vital component of tourism, it is currently of considerable importance to the global economy, due to the benefits derived from tourism activities and their economic and social impact. Many countries have sought to promote this sector and make it one of their future economic options. Cultural heritage is a symbol of identity for individuals and communities and a fundamental element of their memory, linking the past to the present. It embodies the principles and values of the ancestors and passes them on to future generations. Therefore, the revival, preservation and reactivation of cultural heritage remains a major concern for various countries, as it represents an important economic, social and political resource.